The Role of Human Resources and Technological Advancement on Economic Growth - Ridwannudin, Muhammad; Rokhlinasari, Sri; Haerisma, Alvien Septian (Multidiscience : Journal of Multidisciplinary Science, 2025)
This study aims to comprehensively examine the role of human resources and technological advancement in driving economic growth. Employing a qualitative literature review approach, secondary data were gathered from peer-reviewed academic sources, including scholarly journals, international conference proceedings, and academic books published between 2015 and 2025. The findings reveal that human capital development significantly contributes to labor productivity, innovation, and macroeconomic stability. Similarly, technological advancement accelerates economic growth by enhancing production efficiency, reducing operational costs, and creating new market opportunities. The study underscores the critical synergy between high-quality human capital and effective technology adoption as a foundational mechanism for achieving inclusive and sustainable economic development. Policy implications suggest that developing countries should adopt integrated development strategies by investing in education, vocational training, and digital infrastructure, alongside strengthening national innovation systems. Consequently, enhancing both human and technological capacities is essential for building resilient, knowledge-based economies capable of adapting to global dynamics.